Collaborative governance based on farmers' corporations in the development of sorgum areas in east sumba district - Arvianti, Eri Yusnita; Santosa, Budi; Maraniati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: The development of sorghum in the drylands of East Sumba faces complex challenges, particularly regarding limited government resources and weak farmer bargaining power. This study analyzes the effectiveness of the sorghum area development program through a Collaborative Governance perspective, focusing on the role of farmers' corporations. Methods: This research employed a qualitative descriptive method conducted from May to July 2023 in East Sumba Regency. Data were collected through in-depth interviews, participatory observation, and focus group discussions with 15 key informants selected via purposive sampling (farmers, government officials, and private partners). The analysis utilized Ansell and Gash's framework, examining initial conditions, institutional design, facilitative leadership, and collaborative processes. Results: The findings reveal that while the collaboration has successfully initiated the program, it faces critical structural challenges. Initial conditions were marked by information asymmetry and farmer skepticism due to past failures. Although the institutional design adopted a consensus-based voting mechanism, participation remained dominated by government and private actors, leading to passive involvement from less-educated farmers. However, the Agriculture Office's facilitative leadership proved effective in conflict mediation, and the achievement of